Promontorio architecture and the reflective practice - Milheiro, Ana Vaz; Tavares, André 1976-; Lopes, Diogo Seixas 1972-2016; Frampton, Kenneth 1930-; Cera, Nuno 1972-; Magrou, Rafaël 1971-; Safran, Yehuda (Hatje Cantz, 2023)
This publication features projects that the partnership PROMONTORIO developed over the past 30 years. Together they constitute an impressive body of work for various places across Europe, Africa, the Middle East and the USA, ranging from city planning, to culture and education, heritage and conservation, commercial and mixed-use, in addition to hospitality and leisure. The idea of a reflective practice, set forth by PROMONTORIO, summons the ability to critically and ethically reflect on its own actions, while engaging in a process of continuous adaptation and learning. Perceived as a kind of "practicing school" for various generations in Portugal, the practice evolved, in both theory and practice, through the idea that deliberate reflection on experience is essential to cultivate a developmental insight on architecture
Keywords: Promontorio -- Firma; Geschichte 1993-2023; Architektur; Bildband; Werkverzeichnis